Lipidomic analysis of adipose-derived extracellular vesicles reveals specific EV lipid sorting informative of the obesity metabolic state - Alexia Blandin; Isabelle Dugail; Grégory Hilairet; Maharajah Ponnaiah; Valentine Ghesquière; Josy Froger; Simon Ducheix; Lionel Fizanne; Jérôme Boursier; Bertrand Cariou; Marie Lhomme; Soazig Le Lay (Cell Reports, 2023)
Summary: Adipose extracellular vesicles (AdEVs) transport lipids that could participate in the development of obesity-related metabolic dysfunctions. This study aims to define mouse AdEV lipid signature by a targeted LC-MS/MS approach in either healthy or obesity context. Distinct clustering of AdEV and visceral adipose tissue (VAT) lipidomes by principal component analysis reveals specific AdEV lipid sorting when compared with secreting VAT. Comprehensive analysis identifies enrichment of ceramides, sphingomyelins, and phosphatidylglycerols species in AdEVs compared with source VAT whose lipid content closely relates to the obesity status and is influenced by the diet. Obesity moreover impacts AdEV lipidome, mirroring lipid alterations retrieved in plasma and VAT. Overall, our study identifies specific lipid fingerprints for plasma, VAT, and AdEVs that are informative of the metabolic status. Lipid species enriched in AdEVs in the obesity context may constitute biomarker candidates or mediators of the obesity-associated metabolic dysfunctions.